Numerical and model test results for truss spar platform subjected to random waves - Montasir,, O.A.A.; Kurian, V.J.; Shafiq, N. (2009)
Abstract As the research for oil and other natural resources have progressed into deeper waters, the traditional fixed type of offshore structures have become unsuitable and new technologies had to be resorted to. In this study, a truss spar model was tested using regular and random waves in a wave basin and the responses in surge, heave and pitch were measured. A MATLAB program named ‘TRSPAR’ was developed to determine the responses by numerical method. Time domain integration using Newmark Beta method was employed. The platform was modelled as a rigid body with three degrees of freedom restrained by mooring lines affecting the stiffness values. Wheeler stretching formula and modified Morison Equation were used for simulating the sea state and for determining the dynamic force vector. This program was run using the model parameters and it gave results which agreed well with the corresponding results obtained from the test measurements. Keywords: Truss spar platforms, Time domain analysis, Model tests, Modified Morison equations, Linear Airy wave theory.